Prinsip pemerintahan dalam Islam menurut Muhammad Asad - Ahmad Nabil Amir (Penerbit Universiti Kebangsaan Malaysia, 2024)
The paper discusses Muhammad Asad’s work on the principle of Islamic governance and its basic constitution and foundational structure. In this regard, he formulated the constitutional ideas of Islamic state whose constitution contains the provision of Islamic law that practiced and implemented the norms stated in the Quran and hadith. This idea was partly enshrined in the Pakistan constitutional law whose political establishment was formed in 1947. It essentially discussed Muhammad Asad’s political ideas and its underlying philosophy as espoused in his works, such as The principles of state and government in Islam, This law of ours and other essays, Islamic constitution making, journal Arafat, The message of the Quran, Sahih alBukhari the early years of Islam and etc. The study is based on qualitative methods in the form of library research. The data were analysed using descriptive, analytical and comparative methods. The finding shows that Muhammad Asad had formulated comprehensive theoretical framework of legal aspect of Islamic governance drawn up from the fundamental principle and doctrine of the shariah, and its moral norms derived from the teaching of the Quran and the sunnah, while advocating democratic ideals and principles based on conventional practice and requirement of modern context of nation state.